The aftermath of PCV: Current trends and future directions. - Costa, S.; Tomprou, M. (Caucus organized at Academy of Management Conference, 2019)
This caucus will address the challenges of the research in the aftermath of psychological contract violation and aim to identify new research pathways. The goal of the caucus is to engage participants in inclusive participation on the new topics in the area, and encourage opportunities for collaborative research.